Semicontinuous emulsion copolymerization of vinyl acetate and butyl acrylate using different initiators and different chain length emulsifiers - Saraç, A (WILEY-V C H VERLAG GMBH, 2004)
The semicontinuous emulsion copolymerization of vinyl acetate and butyl acrylate (VAc/BuA) (85:15) initiated by thermal initiators ammonium persulfate (APS) and potassium persulfate (PPS) at 70degreesC in the presence of nonylphenol ethoxylates of varying chain lengths (NP-n) and acrylamide partially polymerized (Amol) was investigated. VAc-BuA copolymer latexes were synthesized as two different series in the glass reactor, in the first serie was initiated by APS and PPS was used as initiator in the second serie. The influence of the counterions or initiators and chain lenghts of non-ionic emulsifier on the properties of VAc-BuA copolymer latexes were determined by measuring Brookfield viscosities, weight average molecular weights ((M) over bar (w)), number average molecular weights ((M) over bar (w)), molecular weight distribution and surface tension of latexes to air. The results of copolymer latexes indicated that their physicochemical properties increased with the increasing chain length of nonionic emulsifier for two initiators.
Keywords: core-shell polymers; emulsion polymerization; initiators; non-ionic emulsifier; vinyl acetate; MINIEMULSION COPOLYMERIZATION; LATEX FILMS; POLYMERIZATION PROCESS; CO-POLYMERIZATION; MORPHOLOGY; BATCH; Polymer Science